Tumor volume and cancer stem cell expression as prognostic markers for high-dose loco-regional failure in head and neck squamous cell carcinoma – A DAHANCA 19 study - Morten Horsholt Kristensen; Mia Kristina Sørensen; Trine Tramm; Jan Alsner; Brita Singers Sørensen; Christian Maare; Jørgen Johansen; Hanne Primdahl; Åse Bratland; Claus A. Kristensen; Maria Andersen; Jacob Kinggaard Lilja‐Fischer; et al. (2024)
BACKGROUND AND PURPOSE: Reliable and accessible biomarkers for patients with Head and Neck Squamous Cell Carcinoma (HNSCC) are warranted for biologically driven radiotherapy (RT). This study aimed to investigate the prognostic value of putative cancer stem cell (CSC) markers, hypoxia, and tumor volume using loco-regional high-dose failure (HDF) as endpoint. MATERIALS AND METHODS: Tumor tissue was retrieved from patients treated with primary chemo-(C-)RT and nimorazole for HNSCC in the Danish Head and Neck Cancer Study Group (DAHANCA) 19 study. Tumor volume, hypoxic classification, and expression of CSC markers CD44, SLC3A2, and MET were analyzed. For patients with eligible data on all parameters (n = 340), the risk of HDF following primary chemo-(C-)RT were analyzed by these biomarkers as a whole and stratified for p16-positive oropharynx (p16 + OPSCC) vs p16-negative (p16-) tumors (oral cavity, p16- oropharynx, hypopharynx and larynx). RESULTS: Higher risk of HDF was seen for patients with larger primary and nodal volume (>25 cm3, Hazard Ratio (HR): 3.00 [95 % CI: 1.73-5.18]), high SLC3A2 (HR: 2.99 [1.28-6.99]), CD44 (>30 % positive, HR: 2.29 [1.05-5.00]), and p16- tumors (HR: 2.53 [1.05-6.11]). p16- tumors had a higher CSC marker expression than p16 + OPSCC. The factors associated with the highest risk of HDF were larger volume (HR: 3.29 [1.79-6.04]) for p16- tumors (n = 178) and high SLC3A2 (HR: 6.19 [1.58-24.23]) for p16 + OPSCC (n = 162). CONCLUSION: Tumor volume, p16, and CSC markers are potential biomarkers for HDF for patients with HNSCC treated with (C-)RT. Lower expression of CSC in p16 + OPSCC may contribute to better tumor control.